The phenotypic diversity of three populations of Asian swamp eel Monopterus albus (Zuiew 1793) from West Java and biometrics responses on salinity - Ahmad Fahrul Syarif; Dinar Tri Soelistyowati; Ridwan Affandi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2016)
This research aimed to evaluate the phenotype diversity of Asian swamp eel from West Java and the biometric responses on salinity for aquaculture development. Fish were collected from three different locations, i.e., Cianjur, Sukabumi, and Karawang with body size of 23.05+0.63 cm and weight of 7.58+1.04 g. Truss morphometric measurement was conducted for 30 samples from each location and biometric response on salty water media for 200 individuals. The experiment was performed in the media with different level of salinity, no substrate and with some shelters. Completely randomized design (CRD) with three levels of salinity (i.e. 0, 6, 12 g L-1) and density 1 kg m-2 was used in this study. Rearing was carried out for 30 days with 100% of media was changed every day and fish were fed with silk worms once a day with at satiation manner. The results showed that phenotypic diversity of Asian swamp eels from Karawang and Cianjur was similar, but differ from Sukabumi population. The biometric responses of Asian swamp eel from Karawang showed the superior performance and the best salinity of media for culture without substrate was 6 g L-1. Abstrak Penelitian ini bertujuan untuk mengevaluasi keragaman fenotipe belut asal Jawa Barat serta respons biometriknya dalam pemeliharaan pada media air bersalinitas untuk pengembangan budi daya. Belut ditangkap dari tiga lokasi yaitu Cianjur, Sukabumi, dan Karawang dengan ukuran tubuh berkisar antara 23,05+0,63 cm dan bobot 7,58+1,04 g. Sebanyak 30 ekor setiap populasi digunakan untuk pengukuran truss morfometrik dan 200 ekor untuk pengujian respons biometrik pada media air bersalinitas. Pemeliharaan dilakukan pada media air bersalinitas tanpa substrat dengan pemberian pelindung. Percobaan menggunakan rancangan acak lengkap dengan perlakuan perbedaan salinitas media pemeliharaan yaitu 0, 6, dan 12 g L-1 dengan padat penebaran 1 kg m-2. Pemeliharaan belut dilakukan selama 30 hari dengan penggantian air 100% setiap hari dengan pemberian pakan berupa cacing sutera Tubificidae sebanyak satu kali per hari secara at satiation. Hasil penelitian menunjukkan bahwa belut asal Karawang dan Cianjur mirip berdasarkan keragaman fenotipenya dibandingkan populasi Sukabumi. Respons biometrik belut asal Karawang paling unggul dan media terbaik untuk pemeliharaan belut tanpa substrat adalah media dengan salinitas 6 g L-1.